Regulation and activity of secretory leukoprotease inhibitor (SLPI) is altered in smokers - Meyer, Megan (American Physiological Society, 2013)
A hallmark of cigarette smoking is a shift in the protease/antiprotease balance, in favor of protease activity. However, it has recently been shown that smokers have increased expression of a key antiprotease, secretory leukoprotease inhibitor (SLPI), yet the mechanisms involved in SLPI transcriptional regulation and functional activity of SLPI remain unclear. We examined SLPI mRNA and protein secretion in differentiated nasal epithelial cells (NECs) and nasal lavage fluid (NLF) from nonsmokers and smokers and demonstrated that SLPI expression is increased in NECs and NLF from smokers. Transcriptional regulation of SLPI expression was confirmed using SLPI promoter reporter assays followed by chromatin immunoprecipitation. The role of STAT1 in regulating SLPI expression was further elucidated using WT and stat1(−/−) mice. Our data demonstrate that STAT1 regulates SLPI transcription in epithelial cells and slpi protein in the lungs of mice. Additionally, we reveal that NECs from smokers have increased STAT1 mRNA/protein expression. Finally, we demonstrate that SLPI contained in the nasal mucosa of smokers is proteolytically cleaved but retains functional activity against neutrophil elastase. These results demonstrate that smoking enhances expression of SLPI in NECs in vitro and in vivo, and that this response is regulated by STAT1. In addition, despite posttranslational cleavage of SLPI, antiprotease activity against neutrophil elastase is enhanced in smokers. Together, our findings show that SLPI regulation and activity is altered in the nasal mucosa of smokers, which could have broad implications in the context of respiratory inflammation and infection.